ADAPTATION OF FIRST-YEAR STUDENTS TO THE EDUCATIONAL PROCESS - Elena S. Gebel (Высшее образование в России)
Тhe article discusses the topical problem of adaptation of first-year students to the demands ofhigher education institution. The author dwells on the basic aspects of the development and formation of student's personality that have a decisive influence on first-year student's success in the formation of professional competencies and in future employment. Basing on the results of the statistical surveys the author proposes the tactic and strategy for students' optimal adaptation to study at university.